2014
DOI: 10.1016/j.jallcom.2013.07.179
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of crystallisation of sol–gel derived calcia–alumina binary compounds

Abstract: In-situ High Temperature X-Ray Diffraction (HTXRD) and Differential Scanning Calorimetric (DSC) studies were performed on a sol-gel derived binary compound of a calcia-alumina (C12A7) system consisting of calcium oxide (CaO) and aluminum oxide (Al 2 O 3) in a ratio of 12:7 for in-situ investigation into the phase transformations under progressively increasing thermal activation from room-temperature to 1200°C. The crystallisation of amorphous samples formulated at room-temperature on magnesium oxide (MgO) sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…HT XRD, DSC and DTA methods are well known and very often used for glass crystallization study [17][18][19][20][21][22][23][24][25] and for study of thermal behavior of many kinds of materials. HT XRD analysis was successfully used for study of phase development in many systems [5,22,23,[26][27][28][29][30] and for determination of conversion rate dependence on temperature in yttrium-aluminate glasses and lanthanum-aluminate glasses [5,10,28,29]. Also, the JMAK model is very frequently used to better describe a changes in materials during crystallization [5,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…HT XRD, DSC and DTA methods are well known and very often used for glass crystallization study [17][18][19][20][21][22][23][24][25] and for study of thermal behavior of many kinds of materials. HT XRD analysis was successfully used for study of phase development in many systems [5,22,23,[26][27][28][29][30] and for determination of conversion rate dependence on temperature in yttrium-aluminate glasses and lanthanum-aluminate glasses [5,10,28,29]. Also, the JMAK model is very frequently used to better describe a changes in materials during crystallization [5,[28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, sol-gel method is often chosen for the production of C12A7 powder [17,18]. The crystallisation of C12A7 consisting of calcium oxide (CaO) and aluminium oxide (Al 2 O 3 ) in a ratio of 12:7 takes place at 1100°C and values of 348 and 375 kJ/mol have been estimated from the Kissinger's equation for the activation energies of crystallisation of CaO and Al 2 O 3 components, respectively [19]. However, it has been recently reported that the addition of ethyl acetoacetate (EAA) to the oxide sol reduces the densification oxide gel significantly leading to the prolonged structural relaxation during heat treatment [20].…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis : In the x CaO–(1 − x )Al 2 O 3 system, C5A ( x = 0.83), C3A ( x = 0.75), C12A7 ( x = 0.63), CA ( x = 0.5), and CA2 ( x = 0.33) glass spheres were synthesized by liquid‐quenching CaO–Al 2 O 3 precursors in the aerodynamic levitator furnace. The precursors were prepared by a sol–gel method, using Al(OBu) 3 97% purity and (Ca(NO 3 ) 2 ·4H 2 O) 99% purity. Auxiliary materials were Etac 98% purity, hydrochloric acid with a concentration of 38%, and ethanol with purity of ≥98%.…”
mentioning
confidence: 99%